IN MILITARY PERSONNEL IT WAS CARRIED OUT UNDER UNILATERAL SPINAL-EPIDURAL ANESTHESIA STUDY THE DYNAMICS OF MOTOR AND SENSOR UNIT DURATION IN OPERATION AND POST-OPERATION PERIODS - Rakhmankulov E. J.; Mirrakhimova S. Sh. (Web of Journals Publishing, 2025)
Unilateral spinal block was first described in 1908 by A. Barker using a hyperbaric solution of local anesthetic. To date, there is no single name for this method in the literature. The names used so far include local spinal anesthesia, partial segmental spinal anesthesia, unilateral spinal anesthesia (USA), monolateral spinal anesthesia, and unilateral spinal anesthesia. The distance between the left and right spinal roots is 10–15 mm [7], which allows the roots to be blocked from only one side. However, to achieve a truly unilateral block, certain conditions must be met, as described below.
Keywords: Unilateral spinal blockade , unilateral spinal anesthesia, heart index i, vegetative index.